PROFIL BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN SOAL MODEL TIMSS KONTEN GEOMETRI - Elvin, Cahyanita; Sunardi, S; Sugiarti, Titik (KadikmA, 2018)
Abstract. This research aims to describe the profile of sudent’s creative thinking skill in solving problems of TIMSS model geometrical content. Indonesian students’ achievement in international mathematics test TIMSS were at low benchmark especially in geometrical content. The reasearch subject were 6 randomly selected students of 64 students from Grade 8A and 8B SMPN 1 Bondowoso. Methods of data collection in this research used tests and interviews. Creative thinking skill aspects are fluency, flexibilty, originality and elaboration. Based on the analysis of the data, the results show that 1 student is categorized as very creative (level 4), 3 students are creative (level 3), and 2 students are categorized as quite creative (level 2). The level 4 student (S3) achieved all aspects as well as fluency, flexibility,originality and elaboration. The student gave variation of answers and interprete problems in different prespectives although he did not often get it. The level 3 students (S1, S4, and S6) can achieve fluency, flexibility, and originality aspect. The level 2 students (S2 and S5) tend to achieve two aspects of creative thinking.   Keywords: Mathematics, TIMSS, Creative Thinking, Geometrical Content.